Biomimetic synthesis, antibacterial activity and structure-activity properties of the pyroglutamate core of oxazolomycin - Angelov, P; Chau, Y; Fryer, P; Moloney, M; Thompson, A; Trippier, P (Royal Society of Chemistry, 2012)
Biomimetic intramolecular aldol reactions on oxazolidine templates derived from serine may be used to generate densely functionalised pyroglutamates, which are simpler mimics of the right hand side of oxazolomycin. Some of the compounds from this sequence exhibit in vivo activity against S. aureus and E. coli, suggesting that pyroglutamate scaffolds may be useful templates for the development of novel antibacterials, and cheminformatic analysis has been used to provide some structure-activity data.